Framework multiobjetivo de ranqueamento e comparação de algoritmos de predição de estrutura terciária de proteínas - Marciano, Michelle Duarte (2016)
Determining the tertiary structure of a protein is very important, once that this is the structure that allow us to know the function of a protein on living beings. There are many algorithms that intend to do this prediction, but none of them does it with one hundred percent of accuracy, being a case of NP-complete problem. Even sill not being able to predict the tertiary structure of proteins with total precision, these algorithms are already used in areas such as pharmacology and are extremely important. This project presents a multiobjective framework for the classification and ranking of these algorithms, thus allowing a comparison among them. The goal is to help improving researches in the area, either in individual algorithms or groups of research in the bioinformatics field.